Validation of the German Glasgow Sensory Questionnaire in autistic adults - Isabel Marie Jakob; Veit Roessner; Melanie Ring (BMC Psychiatry)
Abstract Background We validated the German version of the Glasgow Sensory Questionnaire (GSQ), a self-report questionnaire for adults assessing the processing of stimuli regarding hypo- and hypersensitivity in seven sensory modalities. Since the GSQ is intended for the use in autistic adults, we aimed to complement our previous study on students with high and low Autism Spectrum Quotient (AQ; Zeisel et al., BMC Psychiatry 23:426, 2023), by surveying groups of autistic and non-autistic adults, to present the sensory processing profiles of the two groups, to identify the factor structure of the questionnaire in a group of autistic individuals and to identify the diagnostic value of a cut-off score for heightened sensory sensitivity in German autistic adults. Methods A sample of autistic and non-autistic adults (each n = 86) completed the same German version of the GSQ as used in Zeisel et al. (BMC Psychiatry 23:426, 2023), the AQ and the Symptom Checklist-90-Revised. Factor analyses were applied. Results The German GSQ showed good to excellent reliability. While the factor structure could not be confirmed, main findings of other validation studies were replicated: AQ and GSQ scores were moderately to strongly associated, with higher AQ and GSQ scores for autistic than for non-autistic individuals. Autistic individuals also showed more consistency in their sensitivity across sensory modalities. A third of the autistic participants had heightened sensory sensitivity, when a cut-off was set at the 95th percentile of the non-autism group. Conclusions: Overall, this German version of the GSQ can be considered a validated self-report questionnaire assessing sensory sensitivity particularly in autistic individuals. It can be used to assess sensory sensitivity in the diagnostic process of autism spectrum disorder and to assess an individual's sensory needs and strengths for best possible support. Further studies are required, especially to assess the internal structure of the GSQ.